Blind Distributed MU-MIMO for IoT Networking over VHF Narrowband Spectrum - Gao, Chuhan; Hessar, Mehrdad; Chintalapudi, Krishna; Priyantha, Bodhi (MobiCom 2019, 2019)
Longer range, in rural/urban IoT networks, allow a large geographical coverage with only a few base-stations, making their deployment and operation economical. In this paper we explore the 150-174 MHz spectrum for long range IoT networks comprising unlicensed MURS and licensed VHF narrowbands. Range in these bands is boosted by the lower RF frequencies as well as higher transmit powers allowed by the FCC. Through a 400 sq km wide area deployment study, we show that, these spectrum bands can provide > 20× the geographical coverage than that in the 900 MHz ISM band LoRa. Increased range translates to greater uplink IoT device traffic. The key contribution of this paper is a novel technique – Blind Distributed MU-MIMO, that allows capacity to scale with the number of antennas (base-stations) while not requiring any coordinated channel measurements between the devices and IoT base-stations. This requirement is crucial since in IoT networks power constrained IoT devices typically sleep and wake up to transmit short messages in response to unpredictable events without any coordination with the base-stations. We demonstrate the efficacy of Blind Distributed MU-MIMO through a real wide area deployment.